PURUN WOVEN MAKING ACTIVITIES: ANALYSIS OF THE SUSTAINABILITY OF THE PHYSICAL AND SOCIAL ENVIRONMENT IN THE PALM OIL PLANTATION CONFLICT AREA - Rochgiyanti, Rochgiyanti; Mattiro, Syahlan; Effendi, Rusdi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Before the introduction of oil palm plantations, traditionally, the community had developed skills in making purun woven materials whose raw materials came from the wetland environment around where they lived. After the introduction of plantations, the source of raw materials for purun weaving was reduced. This research aims to discover how purun woven can be preserved and the factors that cause the reduction in purun woven production in Barito Kuala Regency. The sustainability of purun woven-making activities not only contributes to the turning of the wheels of the rural economy but also contributes to social science studies. The research was conducted using qualitative methods. The research locations are villages that are centers for making purun weaving in Kuripan District, Barito Kuala Regency, which have been converted into oil palm plantations. Interviews were conducted with purun woven craftsmen, community leaders, and village heads. There were 20 informants. Observations were made of the purun garden and purun weaving activities. The document study was sourced from data from the Central Statistics Agency for Barito Kuala Regency and Kuripan In Figures District and audiovisual recordings related to purun weaving activities. An ethical perspective was used to analyze the data to obtain an overview of the activity of making purun weaving from the researcher's perspective. The results of the research show that people in Barito Kuala Regency can maintain the existence of purun weaving by maintaining purun gardens even though their area is limited, buying purun from other areas, passing down the method of making purun weaving to the younger generation, and innovating purun products. The factors causing the reduction in purun woven production are the reduction in the area of ​​purun plantations due to the conversion of land to oil palm plantations, the difficulty of raw materials, reduced market demand, and unstable selling prices. From the research results, it can be concluded that making purun woven in Barito Kuala Regency can maintain the sustainability of the physical and social environment. This research implies that the tradition of purun weaving can be preserved, and the surrounding environment can be preserved.